Practicing Life History: Krzysztof Zamorski and his Plebanus and the Village - Domańska, Ewa (Sensus Historiae, 2025)
The text proposes an interpretation of Krzysztof Zamorski’s The Plebanus and the Village. A Life History of the Parish Priest of Tenczynek in the Early Eighteenth Century: A Microhistorical Study (2025) as a mature and consistent realization of life history, understood not merely as an interpretive framework but also as a formative research practice. The author demonstrates that this work emerges from Zamorski’s long-term research on the village of Tenczynek and his earlier theoretical writings, in which life history was conceived as a perspective capable of capturing the lived experience (vissuto) of an individual in the past. The central problem addressed in the article is the relationship between life history and microhistory. Life history is presented as a broad, hybrid research perspective that integrates inspirations drawn from the philosophy of life, biosocial history, historical demography, and biographical methods, while social microhistory, close to the practice of Giovanni Levi, serves as the approach or method that enables the realization of this perspective. The author emphasizes that, by drawing on the understanding of history as scienza del vissuto proposed by Carlo Ginzburg and Carlo Poni, Zamorski moves beyond both the commonsense notion of life history criticized by Pierre Bourdieu (the one that produces the “biographical illusion”) and the reductionism of macrosocial structures. The analysis shows that in The Plebanus and the Village, microhistory leads to the reconstruction of “thick experience,” through which the past becomes empathically accessible and the historical narrative retains an ethical and existential dimension. In this sense, life history emerges as a particularly adequate response to the contemporary challenges facing the humanities: it enables the integration of culture and nature, the individual and the structure, experience and social norms, offering history as a reflection on the human condition in an era of polycrisis.